2022
DOI: 10.35631/jistm.729004
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Competitive Advantage During Covid-19 Pandemic: A Preliminary Case Study of Aerospace Manufacturing Industry in Malaysia

Abstract: The coronavirus (Covid-19) hits the world at a stage where companies plans are affected due to unplanned business disruptions and operations and the aerospace manufacturing industry is one of the industries that was hit severely. This paper is a preliminary attempt to investigate the impact of COVID-19 on the competitive advantage of one of the aerospace manufacturing companies as a case study. Through a comprehensive literature study and survey, this paper presents an interpretation of competitive advantage t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Barney and Hesterly (2018) concluded that the best way for a firm to choose its strategy is to follow strategic management principles [37]. Putri Rozita Tahir et al (2022) noted that monitoring globalization is an essential strategic management undertaking, adding that "The strategic management framework is a set of evaluations and decisions that will help the firm find a competitive advantage. The strategic management method of a series collection of analyses and choices will improve the probability [38].…”
Section: Table 1 Interpretations Of the Concept Of "Tourist Destinati...mentioning
confidence: 99%
See 1 more Smart Citation
“…Barney and Hesterly (2018) concluded that the best way for a firm to choose its strategy is to follow strategic management principles [37]. Putri Rozita Tahir et al (2022) noted that monitoring globalization is an essential strategic management undertaking, adding that "The strategic management framework is a set of evaluations and decisions that will help the firm find a competitive advantage. The strategic management method of a series collection of analyses and choices will improve the probability [38].…”
Section: Table 1 Interpretations Of the Concept Of "Tourist Destinati...mentioning
confidence: 99%
“…Putri Rozita Tahir et al (2022) noted that monitoring globalization is an essential strategic management undertaking, adding that "The strategic management framework is a set of evaluations and decisions that will help the firm find a competitive advantage. The strategic management method of a series collection of analyses and choices will improve the probability [38]. Moutinho (1999) stated that long-term plans (those extending ISSN (Print) 2307-6968, ISSN (Online) 2663-2209 Вчені записки Університету «КРОК» №1 (69), 2023 132 beyond 3 years) are generally very strategic in nature.…”
Section: Table 1 Interpretations Of the Concept Of "Tourist Destinati...mentioning
confidence: 99%